A Brief History of Exposure Notification During the COVID-19 Pandemic in the United States, 2020-2021. (November 2022) - Bair, Henry; Wanger, Jenny D.; Shah, Nirav R.
The swift global spread of COVID-19 prompted public health authorities to explore digital technologies to aid in contact tracing for infection control. Exposure notification, a mobile device–based technology that notifies individuals of potential exposure to COVID-19 without requiring personally identifiable information, has been broadly favored because of its relative ease of use, scalability, and protection of personal privacy. Although several exposure notification protocols were developed, a partnership between Google and Apple led to the development of the most widely implemented exposure notification protocol in the world, including in the United States. In this article, we first describe the development of the Google Apple Exposure Notification (GAEN) protocol, noting the value of the discourse among software developers and public health authorities concerning the protocol's design and features. We track states' deployment of GAEN mobile applications (apps) and population-level adoption rates, finding the nationwide rollout of GAEN apps to be more fragmented than anticipated. We then discuss how the limited data collected from these apps make assessments of their effectiveness challenging. Finally, we consider the importance of the federal government playing a greater role in GAEN's early development, emphasize the power of public–private partnerships, and highlight the overriding importance of public messaging over technological details.